Consistency Tradeoffs in Modern Distributed Database System Design: CAP is Only Part of the Story. - Abadi, Daniel (Computer (00189162), 2012)
The CAP theorem's impact on modern distributed database system design is more limited than is often perceived. Another tradeoff—between consistency and latency —has had a more direct influence on several well-known DDBSs. A proposed new formulation, PACELC, unifies this tradeoff with CAP.